Transformando a Sociedade com a Web 3.0: Um Relato de Projeto Inovador de P&D para Transferência do Cuidado do Paciente e Confiança Digital - Lima, Eliomar Araújo de; Graciano Neto, Valdemar Vicente; Rodrigues, Jacson; Corrêa, Sand Luz; Lázaro, Matheus; Costa, Fabio Moreira (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Web 3.0 has emerged as a (r)evolution, transforming Web 2.0 into a more decentralized version of it. Its enabling technologies foster the development of innovative applications with high potential societal impact. In this context, a prospective project was established between the National Telecommunications Agency (ANATEL) and the Federal University of Goiás (UFG) to develop products leveraging Web 3.0 enabling technologies. The main contribution of this paper is to present an experience report on the project and to disseminate the products created, making them publicly available to society and to the Workshop audience. Two main products were developed: dHigeia, in the healthcare domain; and dAurora, in the field of combating disinformation. The results indicate that the decentralized applications developed have significant potential for social impact.